Bis(imidazolidine)pyridine‐CoCl2: A Novel, Catalytically Active Neutral Complex for Asymmetric Michael Reaction of 1, 3‐Carbonyl Compounds with Nitroalkenes. Issue 16 (3rd July 2019) - Arai, Takayoshi; Iimori, Yuko; Shirasugi, Mayu; Shinohara, Ryota; Takagi, Yuri; Suzuki, Takumi; Ma, Junma; Kuwano, Satoru; Masu, Hyuma
Abstract: A neutral bis(imidazolidine)pyridine (PyBidine)‐CoCl2 complex showed catalytic activity for the Michael reaction of malonates with nitroalkenes. The results indicated that a weak amine base aided enolate formation from the neutral complex, in which the N−H proton of the imidazolidine ligand played a significant role. Abstract :